Tourism planning and development - Cruz, Reil G. (Manila, Philippines : Rex Book Store, 2014)
The book was a direct result of a meeting between the officers of REX Publications and the UP Diliman Asian Institute of tourism in 2013. The manuscript was written over a span of 180 days.
Chapter 1 : Basic concepts in tourism planning and development -- Chapter 2 : The Tourism planning process -- Chapter 3 : Approaches to tourism planning and development -- Chapter 4 : Laws relevant to tourism planning -- Chapter 5 : Tourism product development -- Chapter 6 : Forms of tourism -- Chapter 7 : Tourism impact mitigation and adaptation -- Chapter 8 : Tourism impact monitoring -- Chapter 9 : Accessible tourism -- Chapter 10 : Participatory tourism planning.
Includes bibliographical references and index.
Keywords: TOURISM